Tranexamic Acid in Neuroanesthesia and Neurocritical Care: Time for Its Critical Appraisal - Hooda, Bhavna; Muthuchellappan, Radhakrishnan (Journal of Neuroanaesthesiology and Critical Care, 2019)
There is a renewed interest in the use of antifibrinolytics, especially tranexamic acid (TxA), in varied clinical settings such as trauma, perioperative bleeding, cardiac surgery, and multilevel spine instrumentation procedures. Because of its prothrombotic potential, the use of TxA in neurosurgical disorders has not gained popularity since this subset of the population is more prone to developing thromboembolic complications. However, recent studies have shown that TxA reduces blood loss, reduces the need for allogeneic blood transfusion, and is associated with minimal side effects. In this narrative review, Google Scholar, PubMed, and EMBASE databases were searched to identify publications relevant to the current use of TxA in varied neurosurgical and critical care settings. These publications were analyzed, and a summary of the findings and the role of future research on this drug are presented in this review.
Keywords: tranexamic acid; traumatic brain injury; intracerebral hemorrhage; chronic subdural hematoma; subarachnoid hemorrhage; perioperative period